The Prognostic Value of Baseline Distant Metastasis in Icotinib-Treated Patients with EGFR-Mutated Stage IV Non-Small Cell Lung Cancer - Wang L; Shi T; Feng L; Fan Z; Xu X; Zhou X; Zhang X; Han J; Jing L; Liu J; Shan Y; Liu F; et al. (Cancer Management and Research, 2021)
Long Wang,1,* Tiantian Shi,1,* Li Feng,1 Zhisong Fan,1 Xiaoli Xu,2 Xinliang Zhou,1 Xue Zhang,1 Jing Han,1 Li Jing,1 Jiayin Liu,1 Yujie Shan,1 Fengling Liu,1 Jing Zuo,1 Yudong Wang1 1Department of Medical Oncology, The Fourth Hospital of Hebei Medical University, Shijiazhuang, 050011, People’s Republic of China; 2Department of Medical Records, The Fourth Hospital of Hebei Medical University, Shijiazhuang, 050011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yudong Wang Email 15931166600@126.comPurpose: Several studies have revealed the prognostic value distant metastasis in non-small-cell lung cancer (NSCLC) patients receiving first-line epidermal growth factor receptor (EGFR) inhibitors. However, the question of whether the specific metastatic site could predict survival outcomes remain elusive. This study evaluated the prognostic value of specific metastatic site at diagnosis in first-line icotinib-treated patients with EGFR-mutated advanced NSCLC.Methods: A total of 216 patients with EGFR-mutated stage IV NSCLC who received first-line icotinib treatment were retrospectively enrolled. The associations between the presence of distant metastasis to certain organs at diagnosis and survival outcomes were analyzed.Patients and methods: The presence of distant metastases was not associated with progression-free survival. Patients with liver metastasis showed a significantly shorter OS than those without liver metastasis (14.6m vs 33.0m, p=0.024). Patients with brain metastasis showed a marginally shorter OS than those without brain metastasis (26.5m vs 33.8m, p=0.051). Patients with lung metastasis showed a significantly longer OS than those without lung metastasis (36.0m vs 28.6m, p=0.038). Multivariable Cox regression analysis showed the presence of liver metastasis (HR [hazard ratio]: 2.265, 95% CI [confidence interval]: 1.239– 4.139, p=0.008) and brain metastasis (HR: 1.493, 95% CI: 1.012– 2.202, p=0.043) were independent predictors for unfavorable OS, while lung metastasis (HR: 0.669, 95% CI: 0.460– 0.971, p=0.034) was an independent predictor for favorable OS.Conclusion: The presence of liver and brain metastasis predicted unfavorable OS, while the presence of lung metastasis predicted favorable OS in first-line icotinib-treated patients with EGFR-mutated stage IV NSCLC.Keywords: metastasis, non-small cell lung cancer, EGFR mutations, icotinib, prognostic value